Effectiveness of Educational Videos on Improving Elementary School Children’s Knowledge of Safe Touches: A Quasi-Experimental Study - Risna Damayanti; Nuraspina Nuraspina; Erviana Erviana; Eva Yuliani; Sastriani Sastriani; Irna Megawaty (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Sexual violence againts children is one of the increasingly alarming issues that is rising every year. One effective effort needed to prevent the problem of sexual violence is to provide sex education from an early age to both children and parents through safe touches program. The purpose of this research is to determine the effectiveness of educational videos in increasing children’s knowledge about the safe touches. This study employs a quantitative research design with a quasi-experimental approach utilizing the pretest-posttest one-group method. The research was conducted in March 2025 at SD Negeri No. 10 Galung, Banggae subdistrict, Majene regency. The sample consisted of 36 respondents selected using a total sampling method. The research results show that before the intervention 29 (80.6%) children had poor knowledge and 7 (19.4%) children had good knowledge, after conducting the Wilcoxon test, the Asymp.sig (2-tailed) value obtained was 0.001, indicating a significant increase in knowledge after providing video-based education to children about safe touches at SD Negeri 10 Galung. The conclusion of this research suggest that the provision of educational videos effectively increases knowledge about safe touches among elementary school children, thereby reducing the risk of sexual violence in the community.